PROTEIN l-ISOASPARTYL METHYLTRANSFERASE2 Is Differentially Expressed in Chickpea and Enhances Seed Vigor and Longevity by Reducing Abnormal Isoaspartyl Accumulation Predominantly in Seed Nuclear Proteins(1)([W]) - Verma, Pooja (American Society of Plant Biologists, 2013)
PROTEIN l-ISOASPARTYL METHYLTRANSFERASE (PIMT) is a widely distributed protein-repairing enzyme that catalyzes the conversion of abnormal l-isoaspartyl residues in spontaneously damaged proteins to normal aspartyl residues. This enzyme is encoded by two divergent genes (PIMT1 and PIMT2) in plants, unlike many other organisms. While the biological role of PIMT1 has been elucidated, the role and significance of the PIMT2 gene in plants is not well defined. Here, we isolated the PIMT2 gene (CaPIMT2) from chickpea (Cicer arietinum), which exhibits a significant increase in isoaspartyl residues in seed proteins coupled with reduced germination vigor under artificial aging conditions. The CaPIMT2 gene is found to be highly divergent and encodes two possible isoforms (CaPIMT2 and CaPIMT2′) differing by two amino acids in the region I catalytic domain through alternative splicing. Unlike CaPIMT1, both isoforms possess a unique 56-amino acid amino terminus and exhibit similar yet distinct enzymatic properties. Expression analysis revealed that CaPIMT2 is differentially regulated by stresses and abscisic acid. Confocal visualization of stably expressed green fluorescent protein-fused PIMT proteins and cell fractionation-immunoblot analysis revealed that apart from the plasma membrane, both CaPIMT2 isoforms localize predominantly in the nucleus, while CaPIMT1 localizes in the cytosol. Remarkably, CaPIMT2 enhances seed vigor and longevity by repairing abnormal isoaspartyl residues predominantly in nuclear proteins upon seed-specific expression in Arabidopsis (Arabidopsis thaliana), while CaPIMT1 enhances seed vigor and longevity by repairing such abnormal proteins mainly in the cytosolic fraction. Together, our data suggest that CaPIMT2 has most likely evolved through gene duplication, followed by subfunctionalization to specialize in repairing the nuclear proteome.